Determination Of Firm Age, Financial Distress, And Audit Opinions On Audit Delays - Dwi Anggraeni; Zaenal Wafa (Jurnal Akuntansi, 2024)
Property and real estate sectors are among those where delays in releasing financial statements have been prevalent. The reduced business activities during the COVID-19 pandemic have contributed to these delays, which have remained consistently high each year. As a result, many individuals and stakeholders have experienced behavioral shifts, becoming more cautious when making investment decisions. This cautiousness is linked to the postponement of financial statement releases, a key indicator of a company's transparency and confidence in disclosure. Stakeholders also consider factors such as the company's ability to endure difficult circumstances, its resilience against risks that could impact stock prices or performance, and the absence of negative auditor feedback as critical benchmarks. Examining and investigating how audit opinions affect firm age, financial distress, and audit delays is the aim of this research. Representative sample in this study using 85 companies, the study project focuses on property and real estate companies which have been traded on IDX between 2020 and 2022. Descriptive statistical analysis, multicollinearity tests, binary logistic regression tests, and outlier tests were among the techniques used to examine quantitative data. The findings suggest that firm age and financial distress do not contribute to audit delays, while the audit opinion does significant impact on audit delay.